(untitled) (OverHolland, 2013)
Jerzy Gawronski (ed.) Amsterdam Ceramics: a city’s history and an archaeological ceramics catalogue 1175-2011 Amsterdam, Bas Lubberhuizen, 2012, 336 pp. Peter Jan Knegtmans Amsterdam: een geschiedenis (‘Amsterdam: a history’) Amsterdam, SUN, 2011, 440 pp. Peter Jan Knegtmans Amsterdam: een geschiedenis (‘Amsterdam: a history’) Amsterdam, SUN, 2011, 44